Mobilising supplier resources by being an attractive customer: Relevance, status and future research directions. Issue 3 (June 2019) - Pulles, Niels J.; Ellegaard, Chris; Schiele, Holger; Kragh, Hanne
Abstract: For buying companies, supplier resource mobilisation is an essential process in gaining and sustaining preferential access to supplier resources. This editorial provides insights into the processes of supplier resource mobilisation and introduces three empirical studies on supplier resource mobilisation. We first introduce the supplier resource mobilisation cycle. This cycle may serve as a roadmap for purchasing and supply management (PSM) practitioners seeking to improve access to supplier resources. In addition, this article informs PSM scholars about the status of the supplier resource mobilisation literature and proposes avenues for future research. The cycle includes six stages: (1) becoming an attractive customer, (2) segmenting suppliers, (3) generating supplier satisfaction, (4) becoming a preferred customer, (5) engaging in supplier-oriented actions, and (6) integrating supplier resources. Finally, we introduce the articles in this issue that each examine a different stage of the supplier resource mobilisation process. Highlights: Places supplier resource mobilisation at the core of the purchaser's objectives. Offers an overview of the field and provides directions for future research. Provides a resource mobilisation cycle as a roadmap for both practice and theory.